2014
DOI: 10.1523/jneurosci.2291-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Aversive Conditioning during Sleep Reduces Cigarette-Smoking Behavior

Abstract: Recent findings suggest that novel associations can be learned during sleep. However, whether associative learning during sleep can alter later waking behavior and whether such behavioral changes last for minutes, hours, or days remain unknown. We tested the hypothesis that olfactory aversive conditioning during sleep will alter cigarette-smoking behavior during ensuing wakefulness. A total of 66 human subjects wishing to quit smoking participated in the study (23 females; mean age, 28.7 Ϯ 5.2 years). Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 100 publications
1
80
1
4
Order By: Relevance
“…Nevertheless, a recent study showed that sleep-learning could influence behaviour where similar procedures in wakefulness failed. 159 In this study, cigarette-smoking habits were reduced after the pairing of tobacco odour with an aversive odour during sleep but not with similar conditioning in wakefulness.…”
Section: A N U S C R I P Tcontrasting
confidence: 54%
See 1 more Smart Citation
“…Nevertheless, a recent study showed that sleep-learning could influence behaviour where similar procedures in wakefulness failed. 159 In this study, cigarette-smoking habits were reduced after the pairing of tobacco odour with an aversive odour during sleep but not with similar conditioning in wakefulness.…”
Section: A N U S C R I P Tcontrasting
confidence: 54%
“…4,159,160 The public health consequences of sleep-related accidents are severe, with an estimated 30% of fatal motor vehicle accidents partially attributed to sleepiness at the wheel on highways and a lower but significant risk on other roadways. [161][162][163] Because napping is a recognized means of fighting sleepiness, and sleepiness at the wheel is one of the most potentially dangerous situations in daily life, it is easy to understand why napping has been one of the main expert recommendations to prevent sleepiness at the wheel.…”
Section: Napping and Sleep-related Accidentsmentioning
confidence: 99%
“…Although IAT measures are imperfect and may sometimes reflect knowledge of cultural stereotypes rather than implicit bias per se (29), prior research has demonstrated consequences for social behavior such that low implicit bias as measured with the IAT may indeed be linked with egalitarianism (6, 7). Given that training to reduce implicit bias can be conceptualized as a type of habit learning (30), perhaps novel sleep manipulations could be adapted to aid people in changing various unwanted or maladaptive habits, such as smoking, unhealthy eating, catastrophizing, or selfishness (31). …”
mentioning
confidence: 99%
“…For example, one study used evaluative conditioning to associate drinking with unpleasant experience, and found a reduction in craving and consumption [4]. In another study, smoking behavior was reduced by an association induced during sleep in subjects who wished to quit smoking [5]. A recent review of decision making indicates that behavioral changes can occur with or without conscious intention [6].…”
mentioning
confidence: 99%